Distribution and population structure of the juvenile of Diospyros celebica bakh. Under the canopy of their mother-tree - Sitti Saleha; Putu Oka Ngakan (Jurnal Penelitian Kehutanan Wallacea, 2016)
The distribution pattern and population structure of Diospyros celebica under the conopy of their mother[1]tree stand were studied in the experimental forest of Hasanuddin University at Maros District. One hectar rectangular plot was established in the secondary natural forest dominated by D. celebica. All individuals of D. celebica found in the plot were recorded their diameter at hight 130 cm above ground level. Individual less than 130 cm in hight were categorized as seedling and measured their total hight from ground level. Analyzes using Morisita’s Distribution Index (Iδ) resulted in the distribution pattern of D. celebica was clumped for all life-stages (seedling, sapling, pole and tree). Distribution pattern of seedling was found to be not significanly correlated to the slope, but was positively and significantly correlated with the level of canopy cover of their mother-tree stand. Abundance of seedlings were found under the canopy of the mother trees. However, as the individuals grow taller the correlation became weaker, until then the correlation became negative at the tree stage. This study also indicated that for all life-stages, more individual of D. celebica were found on the habitat with steeper slopes, but the correlation was not significant. The abundant number of seedling indicates that this species has a good ability in the natural regeneration process.